Mobile application security - Rubešová, Olga; Pecinovský, Rudolf, 1954-; Suchan, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
The main goal of the thesis is to design and develop a secured mobile application. The application will run on the Android platform and communicate with the web server for the synchronization of the web database with the local database on the mobile device. The application shall establish secured connection to the web database for the synchro-nization of private data. The user can make the actualization of the data then. Local database shall be secured against possible private data leakage. The implementation of the application shall avoid the top mobile security risks and possible security breaches. In the first part of the thesis, the top mobile security risks and the techniques, best practices and tools to prevent those threats will be discussed. The second part of the thesis will focus on the design, implementation and testing of the secured mobile appli-cation for working with private data and its communication with the web server. The proposed design will be verified against the security checklist and validate the preven-tion of top mobile risks. The outcome of the thesis is the design of a secured mobile application proved by the prototype implementation and verified against the security checklist.
Vedoucí práce: Rudolf Pecinovský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses